2020
DOI: 10.18256/2318-1109.2020.v9i1.3856
|View full text |Cite
|
Sign up to set email alerts
|

Utilização do Resíduo de Areia Verde de Fundição no Desenvolvimento de Concreto Espumígeno

Abstract: O principal objetivo deste trabalho foi avaliar a substituição da areia natural pelo resíduo de areia verde de fundição na fabricação de concreto espumígeno. O projeto experimental foi constituído de dois fatores com diferentes níveis: proporção de resíduo de areia verde de fundição em cinco níveis (0%, 25%, 50%, 75%, 100%) e quantidade de espuma em quatro níveis (5%, 10%, 15%, 20% em relação à massa total). A substituição da areia natural foi feita em relação a massa de material. As influências de cada fator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…For the results of dry and saturated densities shown in figures 6 & 7, it can be observed that the higher the foam increment in the sample, the less dense they are, this for the different percentages of substitution of natural sand by the residue of green foundry sand, noting a difference in densities in each mix of approximately 300 kg/ m³, presenting this pattern regardless of the curing method adopted, thus being an influential factor in the densities of the samples the percentage of foam adopted in the mixture [11].…”
Section: Dry and Saturated Densitiesmentioning
confidence: 90%
See 1 more Smart Citation
“…For the results of dry and saturated densities shown in figures 6 & 7, it can be observed that the higher the foam increment in the sample, the less dense they are, this for the different percentages of substitution of natural sand by the residue of green foundry sand, noting a difference in densities in each mix of approximately 300 kg/ m³, presenting this pattern regardless of the curing method adopted, thus being an influential factor in the densities of the samples the percentage of foam adopted in the mixture [11].…”
Section: Dry and Saturated Densitiesmentioning
confidence: 90%
“…However, among the researches conducted with respect to studies on the use of green foundry sand waste (GFSW) to replace natural sand in the development of foamed lightweight concrete, few studies were found in the literature. One study that can be cited is that of [11], which presented the use of GFSW as a viable alternative in the manufacture of foamed concrete to replace natural sand, obtaining significant results regarding compressive strength, above 2.5 MPa and decrease in the percentage of dry and saturated densities by 21% and 14%, respectively. Regarding the use of fines from this waste (GFSW) for the production of foaming cellular concrete, no work was found.…”
Section: Introductionmentioning
confidence: 99%
“…As studies have shown, this waste has the potential to be used in the composition of mortars and in the manufacture of concrete. This practice not only contributes to reducing the volume of waste deposited in landfills, but also highlights the importance of ensuring the proper encapsulation of these materials (Ferrazzo et al, 2023;Lermen et al, 2020;Sithole et al, 2022).…”
Section: Introductionmentioning
confidence: 99%